Vygotsky's theories of play, imagination and creativity in current practice: Gunilla Lindqvist's "creative pedagogy of play" in U. S. kindergartens and Swedish Reggio-Emilia inspired preschools - Monica Nilsson; Beth Ferholt (Universidade Federal de Santa Catarina, 2014)
The ideal of modern western childhood, with its emphasis on the innocence and malleability of children, has combined with various social conditions to promote adult's direction of children's play towards adult-determined developmental goals, and adult's protection of children's play from adults.However, new forms of play, in which adults actively enter into the fantasy play of young children as a means of promoting the development and quality of life of both adults and children, have recently emerged in several countries (Sweden, Serbia (the former Yugoslavia), Finland, Japan and the United States). In this paper we discuss the theoretical support for this new form of activity:we argue thatGunilla Lindqvist's reinterpretation ofVygotsky's theory of play, with its emphasis on the creative quality of play, is unique amongst contemporary Western European and American theories of play. And we describe a series of formative interventions that are both instantiations of this new form of activity and an investigation of its theoretical support, which are being conducted in theUnited States and Sweden. Researchers at the Laboratory of Comparative Human Cognition at the University of California, SanDiego have implemented and studied Lindqvist's creative pedagogy of play in U.S. early childhood public school classrooms. Over the past year the central component of this pedagogy, playworlds, has been introduced and studied in three Swedish Reggio-Emilia inspired preschools. In conclusion, some of the findings from these research projects are presented.